Sistem Informasi Penyewaan Gedungs di The Sultan Convention Center Menggunakan Metode Web Engineering - Rizky Ramadhani; Nyimas Sopiah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The Sultan Convention Center is one of the famous building rental venues in Palembang City with a choice of features including weddings, meetings, birthdays and many more. With super luxurious and classic facilities, this building is in first place in the city of Palembang. But unfortunately booking this building is still manual, consumers who want to book this building must first come to The Sultan Convention Center then meet first with the person in charge of explaining several packages and building prices, then consumers are required to pay a sign, after that the admin immediately makes a schedule and prepares a report to the boss that, there are consumers who book the building at that time with things like this it really makes consumers lose a lot of time, so something that should be made easy becomes complicated. and also, of course, makes The Sultan even more disadvantaged because consumers cannot prepare time to change their schedule if the building has already been rented at the time the consumer wants to book. Therefore, the author's goal is to create an information system that can be used to facilitate the rental of The Sultan Convention Center building in the form of a website. The making of the application uses the Web Engineering software development method which consists of communication, planning, modeling, constructions, and deployment. While the programming language used to make this application is PHP (Hypertext Preprocessor).